Association of Gastric Myoelectrical Activity With Ghrelin, Gastrin, and Irisin in Adults With Metabolically Healthy and Unhealthy Obesity - Abulmeaty, Mahmoud M. A.; Aldisi, Dara; Aljuraiban, Ghadeer S.; Almajwal, Ali; El Shorbagy, Eman; Almuhtadi, Yara; Albaran, Batool; Aldossari, Zaid; Alsager, Thamer; Razak, Suhail; Berika, Mohammed; Al Zaben, Mohamed (Frontiers in Physiology, 2022)
Background and Objective: Functional disturbances of gastric myoelectrical activity (GMA) might exist in obesity. However, studies on its association with the gastric hormones in obesity phenotypes are lacking. The objective was to study the association of GMA with the serum levels of key gastric hormones in different obesity phenotypes. Methods: A total of 139 adults (31.00 ± 11.12 years) were classified into different metabolic phenotypes of obesity: 1) normal weight-lean (NWL group): BMI <25 kg/m2 and the fat-mass index (FMI) ≤9.7 kg/m2 in females and ≤6.3 kg/m2 in males; 2) metabolically obese normal weight (MONW group): BMI <25 kg/m2 and FMI >9.7 kg/m2 in females and >6.3 kg/m2 in males; 3) metabolically healthy obese (MHO group): BMI ≥25 and FMI ≤9.7 kg/m2 in females and ≤6.3 kg/m2 in males; and 4) metabolically unhealthy obese (MUO group): BMI ≥25 and FMI >9.7 kg/m2 in females and >6.3 kg/m2 in males. The GMA was measured at the baseline and post-prandial state using a multichannel electrogastrography with a water load satiety test. The average power distribution by the frequency region and the average dominant frequency were used for analysis. Anthropometric measurements and bioelectric impedance analysis were performed to calculate the FMI and fat-free mass index (FFMI). Serum levels of ghrelin, gastrin, and irisin were measured by ELISA kits according to the manufacturer’s protocol. Results: Compared to the NWL group, gastrin and ghrelin levels were significantly low in the MUO participants, while irisin was significantly high. The EGG showed significantly lower baseline and 20-min normogastria frequencies in the MHO and MUO groups. In the MHO group, baseline duodenal frequency was positively correlated with the gastrin level, while normogastria times were positively associated with the irisin level and negatively associated with the ghrelin level. In the MUO group, percentages of bradygastria frequencies at 10, 20, and 30 min were positively correlated with the BMI and FFMI. This bradygastria was correlated positively with the irisin level and negatively with the ghrelin level. Conclusion: The EGG patterns might be associated with obesity-related gastric hormones in different obesity phenotypes. EGG may be a promising clinical tool in obesity assessment. The association of the EGG patterns with hormonal levels needs further investigation for potential practical uses.